Characterization of the La 1−x Ba x CoO 3−δ (0 ≤ x ≤ 1) System as Cathode Material for IT-SOFC - Setevich, C. (2011)
The influence of temperature and procedure on the phase relationships of LaxBa1-xCoO3-δ with 0 < x < 1.0, oxygen nonstoichiometry, thermal and chemical expansion contributions, in air, and the electrochemical response of electrodes formed by three porous layers LaxBa1-xCoO3-δ /(50:50wt%)LaxBa1-xCoO3-δ+Ce0.9Gd0.1O1.95/Ce0.9Gd0.1O1.95 have been investigated. The crystal structures of samples with 0 < x < 0.5 and x = 1.0 were refined satisfactorily with a single phase. The cubic perovskite could be obtained for the x = 0.5−0.7 furnace-cooled samples (5◦C/min). This phase was found unstable for x = 0.6 and 0.7, in air, at T < 1000◦C. For x = 0.8 and 0.9 a mixture of phases has been obtained. The expansion coefficient reaches a maximum of 26×10-6 K-1 for x = 0.6 and a minimum of 16×10-6 K-1 for x = 0.8 and 0.9 for  T = 20-900°C. AC impedance spectroscopy measurements were carried out in the temperature range of 400 < T < 700◦C. A minimum polarization resistance Rp ∼ 0.065 - 0.075 Ohmcm2 was obtained for 0.4 < x < 0.7 at T = 600°C, which compares very well with the Rp value reported for composites prepared with cobaltites.